War horse - Spielberg, Steven, 1946-; Hall, Lee, 1966-; Curtis, Richard, 1956-; Thewlis, David, 1963-; Watson, Emily, 1967-; Mullan, Peter; Arestrup, Niels; Irvine, Jeremy, 1990-; Cumberbatch, Benedict, 1976-; Williams, John, 1932-; Morpurgo, Michael; Dreamworks Pictures; et al. (Burbank, CA : Touchstone Home Entertainment, 2012)
Set against England and Europe during the First World War, begins with the remarkable friendship between a horse,Joey and a man, Albert, who tames and trains him. When they are forcefully parted, the film follows the extraordinary journey of the horse as he moves through the war.
Title from container.
Based on the novel by Michael Morpurgo.
Originally released as a motion picture in 2011.
Special features: War Horse: the look.
Director of photography, Janusz Kaminski ; editor, Michael Kahn ; music by John Williams.
Emily Watson, David Thewlis, Peter Mullan, Niels Arestrup, Jeremy Irvine, Benedict Cumberbatch.
Keywords: Horses -- Drama; Horse trainers -- Drama; World War, 1914-1918 -- Drama; Feature films; Films for the hearing impaired